Mechanisms underlying intracellular delivery - Carreira, Ana Bárbara de Sousa (2015)
AuNPs are versatile systems used for different biomedical application including imaging, drug and gene delivery. These systems support the intracellular transport of active molecules, a step that is considered one of the crucial problems in drug delivery. Nevertheless, in order to design optimal multifunctional AuNPs for specific and efficient nanomedicine applications, the mechanism by which AuNPs interact with living cells must be fully understand. The main goal of this work consisted in the assessment of the cellular uptake mechanism of 14 nm spherical AuNPs by A549 cells, through fluorescent spectroscopy and microscopy, in combination with quantitative analysis by ICP-MS. TAMRA labeled AuNPs were characterized by UV-visible and fluorescent spectroscopy and the final hydrodynamic diameter of 22.5 ± 0.33 nm was obtained by DLS. Regarding the cellular uptake studies, the AuNPs presented a fast cellular uptake kinetics reaching a saturation point after 6 hours of incubation in A549 cells. Further investigation concerning the internalization mechanism of this AuNPs was evaluated using specific inhibitors for different endocytic pathways. Optimal inhibition was achieved using chlorpromazine, inhibitor of clathrin-mediated endocytosis, resulting in a 23.5 % inhibition of AuNPs after 1 hour of incubation. This preliminary result obtained by fluorescent spectroscopy suggests that these AuNPs were predominantly uptake by clathrin-mediated endocytosis, meaning that other endocytic pathways must be involved in the cellular uptake of this AuNPs. In what cell viability is concern, the prepared AuNPs and the endocytic inhibitors revealed no significant effect on the cell viability in A549 cell line.